Pengaruh Kualitas Pelayanan, Kepuasan dan Kepercayaan Terhadap Loyalitas Nasabah LPD Desa Adat Padang Luwih Kecamatan Kuta Utara Kabupaten Badung - Jimbaranto, Gede Putra; Sumada, I Made; Wirata, Gede (Jurnal Ilmiah Global Education, 2024)
Customer loyalty plays a critical role in facilitating economic activity at the village level, particularly in terms of lending and depositing funds. Customer loyalty contributes to the sustainability and stability of LPDs. The purpose of this study was to analyze the effect of service quality, satisfaction, and trust on customer loyalty. The number of samples used was 100, using the accidental sampling method. Data collection was done using a Likert scale questionnaire. This type of research is quantitative. The data analysis technique uses multiple linear regression analyses. The application used is Smart PLS. Hypothesis testing is done using the t test and the F test. The results showed that service quality has a positive and significant effect on customer loyalty, satisfaction has a positive and significant effect on customer loyalty, and trust has a positive and significant effect on customer loyalty. Service quality, satisfaction, and trust simultaneously have a positive and significant effect on customer loyalty at LPD Desa Adat Padang Luwih. The contribution of service quality, satisfaction, and trust to customer loyalty is 85.6 percent. It is recommended to improve service quality, satisfaction, and trust.